Spermaturia after Radical Prostatectomy: Is Surgical Preservation of Fertility Possible? - Chad Reichard; Edmund S. Sabanegh; J. Stephen Jones; Khaled Fareed (Case Reports in Urology)
Ease of sperm retrieval has not been previously described as a goal for patients undergoing radical prostatectomy for prostate cancer; however preservation of fertility is a known concern for some younger prostate cancer patients. We present the first known case of a patient with postejaculatory spermaturia following robotic assisted radical prostatectomy. We hypothesize that this is due to fistula formation between the vas deferens and the urinary tract.